Kuat Tarik Tidak Langsung Asphalt Concerete Binder Course (AC-BC) Menggunakan Pasir Alam Kampar - Afriansyah, Yuda; Sentosa, Leo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
In Specification of Bina Marga 2010, natural sand can be used as fine aggregate not more than 15% the mixture of total weight. In some areas, especially in the watershed area, it is easy to find natural sand rather than sand or fine aggregate of crushed stone screening, because there is no need crushing process. It just takes to sieved to obtain the size we need. Flexible pavement construction consists of layers were deposited on land that has been compacted which has function to receive traffic load and spread it to the layer below. The impact of load on the traffic so there are tensile stress on pavement, therefore the pavement is expected to has enough strength of sufficient tensile to hold it. The tensile strength can be used as a parameter for assessing the performance of asphalt concrete. This research is to determine the effect of the use on natural sand and how many percent of the optimum sand content obtained in the asphalt mixture type AC-BC by doing indirect tensile strength test. In this research the variation of the fine aggregate type of sand that used is 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, and 40% of the total weight of the mixture of aggregate. The results of this research showed that the addition of natural sand on the mixture would increase the tensile strength up to 20% variation in natural sand. Optimum natural sand content (ONSC) for asphalt concrete mix type AC-BC based on the indirect tensile strength test was 20% and the optimum bitument content (OBC) based on the indirect tensile strength test was 6%.Keywords: Natural sand, asphalt concrete AC-BC, Specification of Bina Marga 2010 and Indirect Tensile Strength.